Carbon Material Adsorbent for Rare Earth Ion Recovery - Huang, Lijinhong (Curtin University, 2024)
Ion-adsorption rare earth ore is a type of metal ores which exists in nature by a special way, with the rare earth elements (REEs) adsorbed on the surface of minerals. The adsorption mechanism of REEs by kaolinite was studied, and three new types of porous carbon adsorption material have been developed. The results highlight the potential of the prepared carbon materials in the broad application of adsorbing and recovering rare earth elements.